MODERNIZATION OF THE PRUM FRAMEWORK FOR DATA EXCHANGE - Bugarski, Tatjana; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
In order to improve cooperation between the competent authorities of the Member States, a mechanism for the exchange of data for the needs of criminal proceedings has been developed at the level of the European Union. Among the elements of that mechanism are the instruments created by the  Prum decisions from 2008. The implementation of these decisions has removed barriers to the cross-border movement of certain categories of information, by allowing the competent authorities of one Member State to allow the competent authorities of another Member State to access and search certain databases. Although the Prum Framework is considered a successful instrument of police co-operation, several significant obstacles have been identified over time that hinder the timely and unhindered exchange of data and thus affect the efficiency of investigations. The paper discusses the necessity and direction of the revision of the Prum framework in order to modernize the instruments of data exchange.
Keywords: police cooperation, data exchange, European Union, criminal procedure